(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The Levocetirizinedihydrochloride is a third-generation, non-sedating antihistamine, developed from the second generation antihistamine cetirizine. Chemically, levocetirizine is simply the isolated levorotary enantiomer of cetirizine. Concentrations of Levocetirizinedihydrochloride in serum and dialysate were determined by HPLC. The maximum serum Levocetirizinedihydrochloride concentration and the time to reach that maximum were 204 µg-1 and 0.75 hr, respectively. The terminal disposition half-life of Levocetirizinedihydrochloride in these patients was 8.3 hrs. The haemodialysis clearance of Levocetirizine was 11.0 ml/min-1. Although this is approximately 27% of the apparent total body clearance of Levocetirizinedihydrochloride in subjects with normal renal function, the fraction of the dose removed by dialysis was only 7.2%. Thus, since haemodialysis does not produce a clinically significantly alteration in Levocetirizinedihydrochloride elimination, no supplemental dose should be necessary after dialysis.